Medical Imaging Workshop for Seniors - James Hogan (Association of American Medical Colleges, 2015)
Abstract Introduction This health education workshop is designed to provide an older adult audience with basic information on imaging modalities commonly ordered in an emergency department setting. In conceiving the workshop and choosing topics, we conducted a needs assessment with volunteer residents of a senior housing facility. The participants expressed a desire to learn about medical imaging that they may encounter during a visit to the emergency department. They also requested an educational format that would allow them to actively participate in the learning process by sharing their own knowledge and experience of the presented topic. Methods The resulting workshop presented here is composed of four parts: warm-up sharing session, facilitator-led presentation, reflection session, and Jeopardy-style game. This format is designed to promote active participation of the audience while providing repetition of the material to boost comprehension. The workshop may be led by any member of the health care team, most appropriately by medical students, residents, or attending physicians. The workshop succeeded in generating and maintaining the interest of older adult participants at the senior housing facility. Results The workshop was well attended, with about 20 residents. During the workshop, many audience members participated in the sharing and reflection sessions, and some reported that information in the workshop had alleviated their concerns regarding diagnostic imaging during visits to the emergency department. Participants performed well on the informal group quiz at the end of the presentation, answering well over half of the questions correctly. Moreover, some participants expressed confidence in their retention of the presentation material. As a group, the participants also performed well on the concluding Jeopardy-style game, again correctly answering over half of the questions. The medical student instructor gained valuable presentation experience and newfound respect for the perceptions and concerns of older adults regarding health care. Additionally, he formed close bonds with some of the participants, which facilitated increased comfort in interacting with older adult patients during his early residency years. Discussion Older adults are the fastest-growing segment of the population and use an increasingly large portion of health care resources. The workshop succeeded in generating and maintaining the interest of older adult participants who expressed a desire to learn about medical imaging that they may encounter during a visit to the emergency department.